Business Performance of Snack Food MSMEs Based On Entrepreneurial Orientation, Motivation and Organisational Commitment in East Bogor Sub-district - Tini Kartini; Sudarijati Sudarijati; Muhammad Ilhan Rivaldi (Universitas KH. Abdul Chalim Mojokerto, 2025)
The aim of it is to analyse the impact of entrepreneurial orientation and motivation on business performance through organisational commitment in snack food MSMEs in East Bogor Sub-district, which has implications for improving business performance. The method used in this research is quantitative. The total sample in this study was 100 respondents using nonprobability sampling techniques and purposive sampling methods. The research data collected from the results of filling out the questionnaire and was analysed with path analysis techniques and the Sobel test. The research results show that: (1) entrepreneurial orientation and motivation have a direct and positive influence on organisational commitment and business performance; (2) organisational commitment has a direct and positive impact on business performance; (3) entrepreneurial orientation and motivation have an indirect and positive impact on business performance through organisational commitment.